The effectiveness of selank in the treatment of adjustment disorder - Verbenko, Georgiy; Verbenko, Viktoriya (Psychosomatic Medicine and General Practice, 2018)
Background. Adjustment disorder (AD) is one of the most common mental disorders. Considering the social and economic situation in Ukraine at present, in almost 50% of the population, there are non-psychotic mental health disorders, and this number tends to increase. Individual risk factors that are particularly important for the AD development include the experience of a significant stress in childhood, problems with mental health in the past, difficult life circumstances, etc. At the same time, pathogenetically approaches to AD therapy are not fully understood. Pathogenetically oriented therapy of AD should be based on neurotransmitter causes and systemic therapeutic approach. The neurometabolic, anxiolytic, and psycho-stimulating action of the regulatory peptide allows it to be used in the therapy of psychogenic adaptation disorders. Methods. Clinical manifestations of the AD were studied in different age groups - 21-34 years (n=153), 35-50 years (n=257), 51-65 years (n=167) using the Patient Health Questionnaire (PHQ) and Questionnaire of Stress Resistance (QSR). For the study on the effectiveness of the selank (a synthetic analogue of the immunomodulatory peptide tuftsin) were included 30 patients with the AD. Main (experimental group) received selank for two weeks; the control group didn’t receive any treatment (wait list). Patients were monitored for additional two weeks after the treatment with an assessment at the end of follow-up. Results. According to the study results, selank significantly reduced PHQ score in patients with AD compared to control group. PHQ scores in the selank group after 2 weeks of follow-up were significantly lower for somatic symptoms (mean score 1.2 vs. 3.6; p<0.05), nutritional problems (0.1 vs. 3.4; p<0.05), and alcohol misuses (0.3 vs. 1.5; p<0.05). Conclusions. The use of the synthetic analogue of the immunomodulatory peptide tuftsin has a therapeutic effect on the somatic and mental symptoms of the adjustment disorder.